STUDENTS’ PERCEPTION OF USING DUOLINGO AS A MEDIA FOR LEARNING VOCABULARY - Maru, Mister Gidion; Kilmas, Feronica; Rombepajung, Paula (SoCul: International Journal of Research in Social Cultural Issues, 2024)
The aim of this research is to determine students' perceptions after using the Duolingo application as a media for learning vocabulary. The research was carried out at SMP Negeri 1 Manganitu in October 2023. The subjects of the research were students of class IX B consisted of 25 students. This research used the Descriptive Quantitative research method. Researcher used questionnaire to collect data. In the questionnaire, there are seventeen statements containing five aspects. In the first aspect, most students gave positive responses. In the second aspect, students gave positive and neutral responses. The third aspect is that the students gave a positive response. In the fourth aspect, students gave positive and neutral responses. And in the fifth aspect, the students gave a neutral response. The data was analyzed using a percentage formula. The findings show that the majority of students responded positively to the statements contained in the questionnaire. In the first, second, third, fourth and fifth statements, most students gave positive responses to each statement. Furthermore, in the sixth, seventh, eighth and ninth statements, most students gave quite positive responses to each statement. Then for the tenth and eleventh statements, the students gave positive responses. Furthermore, for the twelfth, thirteenth, fourteenth and fifteenth statements, most students gave quite positive responses to each statement. And finally, for the sixteenth and seventeenth statements, the students gave positive responses.